Cerebral hemodynamics and pseudo‐continuous arterial spin labeling considerations in adults with sickle cell anemia. (4th January 2017) - Juttukonda, Meher R.; Jordan, Lori C.; Gindville, Melissa C.; Davis, Larry T.; Watchmaker, Jennifer M.; Pruthi, Sumit; Donahue, Manus J.
Abstract : Sickle cell anemia (SCA) is a genetic disorder resulting in reduced oxygen carrying capacity and elevated stroke risk. Pseudo‐continuous arterial spin labeling (pCASL) measures of cerebral blood flow (CBF) may have relevance for stroke risk assessment; however, the effects of elevated flow velocity and reduced bolus arrival time (BAT) on CBF quantification in SCA patients have not been thoroughly characterized, and pCASL model parameters used in healthy adults are often applied to patients with SCA. Here, cervical arterial flow velocities and pCASL labeling efficiencies were computed in adults with SCA ( n  = 19) and age‐ and race‐matched controls without sickle trait ( n  = 7) using pCASL in sequence with phase contrast MR angiography (MRA). Controls ( n  = 7) and a subgroup of patients ( n  = 8) also underwent multi‐post‐labeling‐delay pCASL for BAT assessment. Mean flow velocities were elevated in SCA adults (velocity = 28.3 ± 4.1 cm/s) compared with controls (velocity = 24.5 ± 3.8 cm/s), and mean pCASL labeling efficiency ( α ) was reduced in SCA adults ( α  = 0.72) relative to controls ( α  = 0.91). In patients, mean whole‐brain CBF from phase contrast MRA was 91.8 ± 18.1 ml/100 g/min, while mean pCASL CBF when assuming a constant labeling efficiency of 0.86 was 75.2 ± 17.3 ml/100 g/min ( p  < 0.01), resulting in a mean absolute quantification error of 23% when a labeling efficiency appropriate for controls was assumed. This difference cannot be accounted for by BAT (whole‐brain BAT: control, 1.13 ± 0.06 s; SCA, 1.02 ± 0.09 s) or tissue T 1 variation. In conclusion, BAT variation influences pCASL quantification less than elevated cervical arterial velocity and labeling efficiency variation in SCA adults; thus, a lower labeling efficiency ( α  = 0.72) or subject‐specific labeling efficiency should be incorporated for SCA patients. Abstract : We examined the effect of cervical arterial flow velocity on pseudocontinuous arterial spin labeling (pCASL) labeling efficiency in adults with sickle cell anemia (SCA). Our results showed that flow velocities were higher and labeling efficiencies were lower in adults with SCA relative to controls, resulting in underestimation of cerebral blood flow (CBF) when a labeling efficiency appropriate for controls is assumed. Thus, individualized labeling efficiencies should be computed for SCA adults on an individual basis to ensure reliable CBF measurement using pCASL MRI.